LIGHT QUALITY EVALUATION IN DRAWING WORKSHOPS THROUGH NATURAL AND ARTIFICIAL LIGHTING’S COMBINATION: CASE STUDY, BLOCK 06 WORKSHOPS AT THE UNIVERSITY OF TÉBESSA - Belarbi Lakhdar; Ahriz Atef; Benmicia Nawal; Boudersa Ghani (International Journal of Innovative Technologies in Social Science, 2024)
Daylight is a crucial element in architectural design. The evaluation of daylighting in buildings serves two main objectives. The first is to achieve visual comfort through daylighting, which is most suitable for human physiology. The second objective is to examine energy efficiency and control energy consumption. Daylighting strategies can significantly reduce energy consumption and greenhouse gas emissions by decreasing the lighting and electrical cooling needs of buildings (Jean-Louis Scartezzini, 1993). Appropriate architectural design not only provides access to inspiring visual outdoor information but also contributes significantly to sustainable development by replacing and displacing electrical energy consumption in buildings (Suzel BALEZ 2007). Our study investigates the performance level of the combination of both natural and artificial lighting in design workshops, using both comparative and experimental approaches. The importance of the study aims at reducing energy consumption and energy costs by utilizing natural lighting when possible. Therefore, the overall objective of this research is to improve the quality of light in the indoor space by combining natural and artificial lighting to create a more uniform and balanced lighting. Additionally, this research aims to create a more pleasant indoor environment for occupants through the use of natural light, which can contribute to their well-being and health.